Indonesian Senior High School Students’ Attitude towards Literature in English - Silva Afdian; Delvi Wahyuni (Universitas Negeri Padang, 2020)
This study aimed to investigate senior high school students’ attitude towards advantages of learning literature in English. The participants of this research were 22 eleventh grade students in SMAN 2 Padang who took English as Specialization class. This study was descriptive qualitative research used in investigating senior high school students’ attitude towards literature in English. The instrumentations of this research were questionnaire and interview. The following are advantages of learning literature in English, encouraging language sources, improving language skill, expanding students’ awareness through environment and willingness to learn English language. The findings of the research showed that students’ attitude towards advantages of learning literature in English is positive.